Screening Of Extrapulmonary Tuberculosis Samples by Zeihl Neelsen Staining in Patients Presenting at Tertiary Care Hospital Ahmedabad - Patel, Lata R; Panchal, Jignesh A.; Pethani, Jayshree D.; Rathod, Sanjay D.; Patel, Parimal H.; Shah, Parul D. (National Journal of Community Medicine, 2013)
Context: Along with pulmonary tuberculosis now extrapulmoanary variety continues to be a major health problem in our country & is emerging from the shadows of its senior cousin. Diagnosis of EPTB has always been a challenge. The aims of the present study was to detect the acid fast bacilli by zeihl neelsen and positive samples were confirmed by fluorescent staining from various unsuspected extrapulmonary specimens at our hospital, and to investigate their demographic characteristics. Objectives: To detect the acid fast bacilli by zeihl neelsen staining in extrapulmonary samples and to investigate their demographic characteristics. Methods and Material: A retrospective analysis was carried out during January 2011 to June 2011. All extrapulmonary samples were screened for acid fact bacilli by 20% Z-N stain and positives were confirmed by fluorescence microscopy. Results: Total 793 extrapulmonary samples received during 1st January 2011 to 30th June 2011, from which 18 (2.26%) samples were found to be positive including 14(1.76 %) pus, 3(0.37%) pleural fluid & 1(0.13%) ascitic fluid. Common age group was 10 to 30 yrs. and Female : male ratio was 1.5:1. From total positive, 11% were HIV positive patients. Conclusions: However, based on our results TB Control Programme might usefully target young populations for early diagnosis of EPTB to decrease TB morbidity and mortality.